FEATURES (CHARACTERISTICS) OF AUTHENTIC VIDEO MATERIALS IN ENGLISH LANGUAGE TEACHING - Dusmurodova Iroda Kuvonovna (Modern American Journals, 2025)
This study explores the key features of authentic video materials used in English language teaching. Authentic videos provide realistic language input, including natural speech, slang, and varied accents. They expose learners to cultural contexts and non-verbal cues such as gestures and facial expressions. These materials illustrate pragmatic functions like politeness and requests in real communication. Authentic videos engage learners through relevant and motivating content. Teachers report that these videos improve listening skills and cultural awareness. However, difficulties arise due to fast speech and unfamiliar vocabulary. Scaffolding and pre-teaching are essential for effective use. The research involved analyzing diverse video clips and interviewing 20 ELT teachers. Results show that authentic videos enhance communicative competence beyond grammar. They offer multimodal input combining visual and auditory information. Exposure to different accents fosters adaptability. Videos enrich learners’ pragmatic and intercultural skills. Teachers emphasize the need for careful video selection. Despite challenges, authentic materials motivate students. They bridge the gap between classroom learning and real-world language use. Future studies should focus on teaching strategies for diverse learner levels. Overall, authentic videos are valuable in modern English language classrooms.
Keywords: authentic video, Language teaching methods, Language learning motivation, language teaching, audiovisual input, ELT resources